2023
DOI: 10.1101/2023.11.14.567134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Adeno-Associated Virus Genome Quantification with Amplification-Free CRISPR-Cas12a

Zach Hetzler,
Stella M. Marinakos,
Noah Lott
et al.

Abstract: Efficient manufacturing of recombinant Adeno-Associated Viral (rAAV) vectors to meet rising clinical demand remains a major hurdle. One of the most significant challenges is the generation of large amounts of empty capsids without the therapeutic genome. There is no standardized analytical method to accurately quantify the viral genes, and subsequently the empty-to-full ratio, making the manufacturing challenges even more complex. We propose the use of CRISPR diagnostics (CRISPR-Dx) as a robust and rapid appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The gel image in Figure S5 confirmed that supercoil relaxation of ΦX174 is equally valid for dsDNA targets. Then, we chose two real-life viral genomes AAV 78 and HPV 16 47 and used their genetic markers (see the sequences in Table S1 ) as the model targets to challenge rCRISPR. The gel image in Figure 7 shows that DNA supercoil relaxation mechanism is universally effective for both targets.…”
Section: Resultsmentioning
confidence: 99%
“…The gel image in Figure S5 confirmed that supercoil relaxation of ΦX174 is equally valid for dsDNA targets. Then, we chose two real-life viral genomes AAV 78 and HPV 16 47 and used their genetic markers (see the sequences in Table S1 ) as the model targets to challenge rCRISPR. The gel image in Figure 7 shows that DNA supercoil relaxation mechanism is universally effective for both targets.…”
Section: Resultsmentioning
confidence: 99%